New Fiscal Package in Kosovo and Its Impact on Economy - Nimani, Artan; Kukaj, Halil (European Journal of Sustainable Development, 2019)
In order to create a more flexible system for citizens and businesses in Kosovo, the Government of Kosovo made a decision by which from 1 April 2014 increased the salaries for 25% for employees receiving salaries and pensioner compensation and other social categories from the Kosovo budget. This Government decision carries some problems with regard to public finance management and impact on the country's economy by creating a new reality in the payroll and public spending. Direct impact of this document: Decision No: 01/176. 10 March 2014, are: First, the increase in wage expenditures was not planned in the Medium Term Expenditure Framework 2014-2016 and this has given an indication of macroeconomic inefficiency (Assessed by the Kosovo Finance Ministry). Secondly, this increase decreases capital investment costs, which have the greatest potential to generate economic growth. Thirdly, wage growth along with spending on the Pristina-Skopje highway is expected to increase the budget deficit over the fiscal rule. Such a situation was also present at the time of investments in the Motorway Vermicë - "Nations connection way". In order to balance the increase of budget expenditures with revenues, the International Monetary Fund (IMF), at the conclusion of the Kosovo visit in March 2015, suggested to the Government of Kosovo that in the continuation of the increase of the various excise duties to see the possibilities for growth Value Added Tax (VAT) which would bring a substantial increase in budget revenues. At the 20th meeting of the Government of Kosovo, dated 24 March 2015, during this IMF visit, the Government took a series of decisions on fiscal changes. Among other things, these decisions have to do with the approval of new draft laws: 1. Changes in Value Added Tax (VAT); 2. Changes in Corporate Income Tax; 3. Changes in Personal Income Tax; and 4. Changes in excises duties of cars, tobacco, and alcoholic beverages etc. Based on the analysis of these changes and their effects, one can make an assessment of the economic and fiscal effects of the aforementioned laws. Some of the key findings of this study-analysis section show that small businesses will be negatively impacted by lowering the VAT threshold, while the abolition of VAT on machinery and raw materials will lower the cost of production and potentially increase investments in manufacturing sectors. Reform in fiscal policy encourages greater investment in production and at the same time improves business liquidity. According to an estimate by the Ministry of Finance, businesses will have about 27.6% cheaper start of production process. Keywords: Kosovo budget.,VAT, Tax, IMF, Ministry of Finance, fiscal